2022
DOI: 10.1684/epd.2021.1369
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of real‐world effectiveness of perampanel in Japanese adults and older adults with epilepsy

Abstract: Objective. While previous studies have demonstrated the safety and effectiveness of perampanel (PER) in combination with other anti-seizure medications in adult patients, data for older patients are limited. This study aimed to confirm real-world safety and effectiveness of combination treatment with PER in Japanese patients with focal seizures with or without focal to bilateral tonic-clonic seizures (FBTCS) or generalised tonic-clonic seizures (GTCS) according to age subgroups (<65 and !65 years of age). Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 23 publications
7
31
0
1
Order By: Relevance
“…The largest observational study to date investigated the efficacy and safety of long-term adjunctive perampanel treatment in Japanese patients who have epilepsy with focal seizures, with or without focal to bilateral tonic-clonic seizures or generalized tonic-clonic seizures (N=3716). 24 In a subgroup analysis of patients aged ≥65 years (n=690), the mean dose of perampanel used was 3.0 mg/day and the mean maximum dose was 3.5 mg/day – both of which were lower than those used in patients <65 years old. The 50% responder rates were higher in the elderly patient group, regardless of seizure type.…”
Section: Key Clinical and Real-world Evidence On Perampanelmentioning
confidence: 95%
See 4 more Smart Citations
“…The largest observational study to date investigated the efficacy and safety of long-term adjunctive perampanel treatment in Japanese patients who have epilepsy with focal seizures, with or without focal to bilateral tonic-clonic seizures or generalized tonic-clonic seizures (N=3716). 24 In a subgroup analysis of patients aged ≥65 years (n=690), the mean dose of perampanel used was 3.0 mg/day and the mean maximum dose was 3.5 mg/day – both of which were lower than those used in patients <65 years old. The 50% responder rates were higher in the elderly patient group, regardless of seizure type.…”
Section: Key Clinical and Real-world Evidence On Perampanelmentioning
confidence: 95%
“…While falls have been reported to occur more frequently in elderly than adult patients on perampanel in clinical trials, 17 real-world analyses have not found this to be the case. 20 , 24 Such discrepancies could be explained by the high dosing (8–12 mg/day) and fast titration (daily dose uptitrated at 2 mg each week) 17 that are characteristic of the clinical trials. 20 This underpins the importance of the “start low and go slow” strategy for elderly patients.…”
Section: Best Practice Expert Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations